CFD characterization and optimization of the cavitation phenomenon in dredging centrifugal pumps (2019)
A model has been developed to characterize the cavitation phenomenon in dredging centrifugal pumps. The operating parameters of a cutter type dredger: swing speed, dredging depth, and inclination, impeller rpm, as well as slurry characterizations such as density and velocity, are introduced, to determine how they influence the operation of the dredge pump. The geometric characterization of the hydraulic transport system of the dredger was performed. With the dredge operational ´s parameters, along with the geometric characterization, the pump is modeled in CFD turbomachinery software. To validate the operational points, the CFD model considers the RNG k-e model and the cavitating-multiphase flow. Through the central composite experiment design, the operating conditions range of the dredger is determined, in which the pump can operate and cavitate. This allows validating the model for different operational points. Finally, multiple regression shows the influence of each of the variables in the response obtained. Furthermore, the regression allows an understanding that operating conditions of the dredger must be adjusted to mitigate the phenomenon of cavitation in the dredging process.